EKSPOR KOPI DAN KARET DI INDONESIA - Ichsan Muhendra Putra; Aliasuddin Aliasuddin (Fakultas Ekonomi dan Bisnis UNSYIAH, 2021)
AbstractThis study aims to analyze the effect of exchange rates and foreign income on coffee and rubber exports in Indonesia. The data used is in the form of quartal data from 2005Q1-2020Q2. This research uses the Autoregressive Distributed Lag (ARDL). The results of this study are long-term estimates, the coffee model found that foreign income has a positive and significant and elastic effect on coffee exports. Meanwhile, the rubber model found that the exchange rate had a negative and significant effect and foreign income had a positive and significant effect. The two variables in the rubber model are elastic. Short-term estimation in the coffee model shows that the two variables do not have a significant effect. In contrast to the rubber model, only the exchange rate which is consistent with the long term has a negative and significant effect. Therefore, the recommendation of this study is that the government needs to maintain exchange rate stability and build cooperation with high-income countries in the export of coffee and rubber. Keyword : Export, Exchange Rates, Gross Domestic Product.